Transient Stability Enhancement Using Matrix Converter Based UPFC with Intelligent Controlling Techniques - Salma, S. K.; Rani, K. Radha (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
This paper presents a matrix converter based UPFC for enhancing the transient stability. Conventional methods use a two step based UPFC (DC-AC-DC). In the proposed model the conventional UPFC is replaced by a Matrix Converter which is controlled with two different controllers which include fuzzy logic controller and the other with an added integrator which is referred to be a HYBRID fuzzy logic controller. In this paper, the working of matrix converter based UPFC with the two controller techniques under certain disturbances is observed using the MATLAB software and the results are verified.